A classification of groups of clowns for teaching-learning in Cuba - Amado González, Miguel Angel (2023)
The article proposes a classification of groups of clowns according to their locations. It is the result of the theoretical and methodological research sustained in different training actions at the National Clown School of Cuba, from the need to strengthen the teaching-learning of this scenic specialty in the different academies in which it is currently taught. The proposal are fundamentally based on the history of the clown with critical references in the Cuban experience.